Principles for information technology investment in u.s. federal electronic records management - Van Wingen, Rachel Senner; Hathorn, Fred; Sprehe, J.Timothy (Journal of government information, 1999)
Changing business and legal conditions force federal agencies to acquire information technology (IT) systems today that may be subject to future mandatory electronic records management (ERM) requirements. Agencies must devise IT investment strategies that optimize operating efficiencies and customer service improvements in the present and also comply with the likely future direction of ERM regulations. The U.S. Environmental Protection Agency undertook a business process reengineering (BPR) exercise with respect to future co-location of previously separate regulatory docket facilities. Their experience suggests that future mandatory ERM will cause federal agencies to take a more thorough account of the full information life cycle when planning an IT system’s life cycle; and that BPR is a practical necessity when implementing ERM.